Hrd1 and ER-associated protein degradation, ERAD, are critical elements of the adaptive ER stress response in cardiac myocytes - Doroudgar, Shirin; Völkers, Mirko; Thuerauf, Donna J.; Khan, Mohsin; Mohsin, Sadia; Respress, Jonathan L.; Wang, Wei; Gude, Natalie; Müller, Oliver J.; Wehrens, Xander H.T.; Sussman, Mark A.; Glembotski, Christopher C. (Circulation research, 2015)
Rationale: Hydroxymethyl glutaryl-coenzyme A reductase degradation protein 1 (Hrd1) is an endoplasmic reticulum (ER)-transmembrane E3 ubiquitin ligase that has been studied in yeast, where it contributes to ER protein quality control by ER-associated degradation (ERAD) of misfolded proteins that accumulate during ER stress. Neither Hrd1 nor ERAD has been studied in the heart, or in cardiac myocytes, where protein quality control is critical for proper heart function.Objective:The objective of this study were to elucidate roles for Hrd1 in ER stress, ERAD, and viability in cultured cardiac myocytes and in the mouse heart, in vivo. Methods and Results: The effects of small interfering RNA–mediated Hrd1 knockdown were examined in cultured neonatal rat ventricular myocytes. The effects of adeno-associated virus–mediated Hrd1 knockdown and overexpression were examined in the hearts of mice subjected to pressure overload–induced pathological cardiac hypertrophy, which challenges protein-folding capacity. In cardiac myocytes, the ER stressors, thapsigargin and tunicamycin increased ERAD, as well as adaptive ER stress proteins, and minimally affected cell death. However, when Hrd1 was knocked down, thapsigargin and tunicamycin dramatically decreased ERAD, while increasing maladaptive ER stress proteins and cell death. In vivo, Hrd1 knockdown exacerbated cardiac dysfunction and increased apoptosis and cardiac hypertrophy, whereas Hrd1 overexpression preserved cardiac function and decreased apoptosis and attenuated cardiac hypertrophy in the hearts of mice subjected to pressure overload. Conclusions: Hrd1 and ERAD are essential components of the adaptive ER stress response in cardiac myocytes. Hrd1 contributes to preserving heart structure and function in a mouse model of pathological cardiac hypertrophy.